The Effect of Transformational Leadership and Passion on Teacher Performance in Public Elementary Schools in Mataram City - Saputra, Heri Hadi; Jaelani, Abdul Kadir; Makki, Muhammad; Note, Hafsiahnor Pua (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Teacher performance is a critical determinant of educational quality, yet empirical studies integrating transformational leadership and teacher passion particularly in basic education settings remain limited. Existing research primarily emphasizes leadership effects, while the psychological mechanisms associated with passion, especially harmonious passion grounded in autonomous motivation, have received insufficient attention. This study examines the effect of transformational leadership and harmonious professional passion on teacher performance in public elementary schools in Mataram City. Using a quantitative survey design, data were collected from 321 teachers selected through simple random sampling. Multiple linear regression analysis shows that both predictors significantly influence teacher performance, with passion demonstrating the stronger effect, indicating that intrinsic motivation and internalized meaning play a more substantial role than external leadership stimuli. These findings extend educational leadership theory by highlighting passion as a central motivational pathway through which performance is sustained, particularly in resource-constrained school environments. While transformational leadership contributes by strengthening collective efficacy and shared purpose, passion functions as an internal driver of persistence and professional commitment. Methodological limitations include the cross-sectional design, reliance on self-reported measures, and lack of moderator analysis for employment status differences (PPPK vs. PNS). The study contributes to the literature by integrating leadership and motivational psychology to explain performance variations, offering implications for leadership development and teacher professionalization policies.